Environmental impact assessment practices of the federative republic of Brazil: A comprehensive review - Ebenezer Ebo Yahans Amuah; Isaac Kow Tetteh; Janet Afia Boadu; Solomon Nandomah (Environmental Challenges, 2023)
The Rio Earth Summit 1992 produced a monumental document, Agenda 21 and 27 PRINCIPLES, where PRINCIPLE 17 describes the Environmental Impact Assessment (EIA). Undoubtedly, Brazil would have been influenced by the outcomes of the Summit to improve her EIA practices. EIA presents empirical decision-making methods geared toward protecting the environment and the well-being of people using prospective or retrospective approaches. This study entailed a retrospective assessment of the EIA system of Brazil using a systematic approach. It covered sectorial, case, and content analyses of the EIA system, a comparison between the EIA of Brazil and the United States of America (USA), proposed amendments in the EIA process of Brazil, possible consequences resulting from the proposed amendments, and gaps and challenges in the EIA process of Brazil. The findings showed that the EIA of Brazil follows a three-step process, and the adoption of EIA has significantly influenced the health, energy, mining, navigation and port, oil and gas, landfill and sand extraction siting, and transport sectors. However, the EIA structure has been under pressure, driven by a demand for amendment and improvement following prominent groups’ requests to suggest momentous reforms to the environmental licensing (EL) and Impact Assessment (IA) processes. Proposals have been presented to reform and redesign the existing EIA system and procedures. However, they did not tackle geopolitical, technical, and budgetary challenges and priorities to tackle the most pressing problems, and information on EIA-related issues is poorly communicated to stakeholders and the public. These have declined stakeholder involvement, participation, and contribution to the EIA process. This review showed that less consideration is placed during EIA regulation implementation for proper harmonization of implementation processes at the federal, state, and local levels.